Changes in Life Expectancy in Moldova During the COVID-19 Pandemic - Ștîrba, Vitalie (Calitatea Vieții, 2023)
During the COVID-19 pandemic, the number of deaths in Moldova has considerably increased in absolute and relative numbers, compared with previous years. Earlier trends in mortality decline worsened for both sexes, while life expectancy decreased by 1.0 years in males and 1.7 years in females, respectively. Comparing the age components in the life expectancy change between pre-pandemic and pandemic periods, we can notice a slight increase in life expectancy in young-population age groups, mainly resulting from external mortality diminution. On the contrary, a sharp decline in life expectancy is observed in both sexes in the ages above 45. Life expectancy diminution was mainly conditioned by increased deaths from coronavirus disease and health system overload, which in many cases led to postponement in planned chronic disease treatment and emergency medical aid. A significant decrease in the number of deaths caused by COVID-19 was highlighted once a considerable proportion of the population was vaccinated against the coronavirus disease. Even though life expectancy is expected to increase in the following years, acquired chronic diseases or their late diagnosis during the COVID-19 pandemic can adversely affect the population’s health in the medium and long term. The paper describes the life expectancy change in Moldova during the COVID-19 pandemic, for which the method of decomposition was used.